A stratocumulus to cumulus transition during a cold-air outbreak: The role of aerosols - Bossioli, Elissavet; Sotiropoulou, Georgia; Karalis, Michail; Abel, Steven J. (Atmospheric Research, 2025)
Cold air outbreaks (CAOs) are phenomena that occur across high latitudes during winter months and favor the development of extensive boundary layer clouds. As the boundary layer evolves, changes in cloud morphology often result in a stratocumulus to cumulus transition (SCT). The onset of precipitation is considered to be a key factor that leads to the break-up of the stratocumulus deck. In this modeling study we investigate the additional role that aerosols have on the SCT within a CAO event in the North Atlantic, by using prognostic fields for both aerosols and cloud droplet number concentrations (Nd). By using two chemical/aerosol schemes we assess and quantify the impact of aerosols on the SCT evolution. Our results indicate that the aerosol load and its chemical composition affect the timing of precipitation initiation and its magnitude and thus the break-up. However, the two schemes reveal contradictory results, which are mainly associated with different aerosol size and chemical composition partitioning between modes and bins. The simulations with the aerosol scheme, which considers the modal approach, show that the reduction of Nd across the SCT is driven by changes in the cloud liquid water content, the sulfate availability, and the fine sea-spray availability in the cumulus region, which suppresses sulfate activation. The Nd decreases mostly follow the decrease in accumulation-mode aerosols. For the scheme that considers the sectional approach, both the stratiform and the cumulus clouds appear sensitive to new particles formation and their competition for water. However, in the cumulus region, the higher updrafts and the greater availability of fine sea salt particles become critical for the activation of small particles. New particle formation and background sulfate concentrations are critical in this pristine environment, while sea salt particles have a significant impact on SCT in both sets of simulations.
Keywords: Aerosol cloud interactions; Aerosols; Cold-air outbreak; MOSAIC aerosol scheme; Precipitation; Prognostic cloud droplets; Sea salt; Stratocumulus-to-cumulus transition; WRF-Chem